The lived religion of polish sex-trafficked survivors: a targeted investigation for practical theological analysis - Deventer-Noordeloos, Farah (Practical theology, 2018)
Sex trafficking is a crime that not only impacts victims physically or psychologically but also spiritually. This article surveys the Polish Catholic context for sex trafficking alongside Christian responses to it with background interviews from those in anti-trafficking work. Analysis from a lived religion perspective is offered on how three Polish female survivors of sex trafficking talk about God in testimony. Their religious and cultural context also is considered when analyzing their narratives. Taken together the survivors and their supporters words reveal the vital themes of love and forgiveness. First forgiveness brings about love, which then stimulates the possibility of a new narrative identity construction. The freedom that a new narrative ushers in is transformative.